Do Sardinella aurita spawning seasons match local retention patterns in the Senegalese–Mauritanian upwelling region?. (January 2015) - Mbaye, Baye Cheikh; Brochier, Timothée; Echevin, Vincent; Lazar, Alban; Lévy, Marina; Mason, Evan; Gaye, Amadou Thierno; Machu, Eric
Abstract Sardinella aurita is the most abundant small pelagic fish in the Senegalese–Mauritanian region. The success of its reproduction crucially depends on the local circulation as this determines whether larvae reach coastal nursery areas favorable to their survival or are dispersed into the open ocean. As a first step towards evaluating sardinella vulnerability to climate‐driven hydrodynamical changes, this study aims at underpinning how transport pathways drive optimal spatial and seasonal patterns for sardinella reproduction. We have used two estimates of the Senegalese–Mauritanian coastal seasonal circulation simulated by two hydrodynamical model configurations that differ in their forcing and topography. Nursery areas are determined by evaluating coastal retention with a Lagrangian individual‐based model that accounts for processes such as diel vertical migration and mortality as a result of lethal temperature exposure. Our results suggest that the shelf zones located at the Arguin Bank (19.5°N–21°N) and south of Senegal (12°N–14.75°N) are highly retentive. We find maximum retention rates in July–August and November–December over the Arguin Bank; from February–July and November–December over the southern Senegalese shelf; and lower retention rates over the central region (14.75°N–19.5°N) that are locally maximum in June–July when the upwelling weakens. These retention areas and their seasonality are in agreement with previously reported spawning patterns, suggesting that the Sardinella aurita spawning strategy may result from a trade‐off between retention patterns associated with the seasonal circulation and food availability. Exposure to lethal temperatures, although not well studied, could be a further limiting factor for spawning. The Lagrangian analysis reveals important connectivity between sub‐regions within and south of the system and hence underlines the importance for joint management of the Sardinella aurita stock.